Alcohol and marijuana protective behavioral strategies mediate the relationship between substance use identity and use-related outcomes: A multi-sample examination. (January 2021) - Montes, Kevin S.; Dela Cruz, Margott; Weinstein, Andrew P.; Pearson, Matthew R.; Lindgren, Kristen P.; Neighbors, Clayton; ,
Highlights: MOD PBS mediated relationship between identity and alcohol-related outcomes. Marijuana PBS mediated relationship between identity and marijuana-related outcomes. Cross-sectional mediation effects were partially replicated longitudinally. Abstract: Substance use identity has been consistently associated with problematic substance use. Limited attention has considered mechanisms of this association. This research examined whether greater identification as a drinker or marijuana user would be associated with the use of fewer alcohol/marijuana protective behavioral strategies (PBS; e.g., avoiding drinking games/avoiding using marijuana in public places). Further, PBS have been associated with lower levels of negative alcohol/marijuana-related outcomes (i.e., frequency, quantity, consequences). In the current multi-sample study, PBS were examined as a mediator of the relationship between drinking/marijuana identity and alcohol/marijuana-related outcomes across three studies. Study 1 was an intervention study with heavy drinking college students ( N = 605), Study 2 was a multisite study of marijuana outcomes among college students ( N = 2, 077), and Study 3 was a study of substance use in a community sample ( n = 369alcohol ; n = 146marijuana ). Cross-sectional and/or longitudinal data were collected across studies. Substance use identity, PBS, and use-related outcomes were measured across the three studies. Indirect effects were evaluated by Monte Carlo confidence intervals. Manner of Drinking PBS were found to be the only statistically significant mediator of the relationship between drinking identity and alcohol-related outcomes (i.e., quantity and consequences) cross-sectionally. These significant cross-sectional mediation effects for alcohol were replicated in one of three longitudinal models. Marijuana PBS were also found to mediate the relationship between marijuana identity and all marijuana-related outcomes examined in the current study. Study findings may help to inform the development of identity-based and PBS-based interventions that aim to reduce negative alcohol/marijuana-related outcomes.